A novel marker technique : using miniature inverted-repeat transposable elements (MITEs) in combination with resistant gene analogues (RGAs) - Lambert, Carol-Ann (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2001.